Control of fungi associated with green gram seeds by using Trichoderma species - Patil, D P; Muley, S M; Pawar, P V (Current Botany, 2012)
In the recent years, the biological control has received a worldwide attention and is being integrated effectively with other pesticides. Moreover, in the context of environmental pollution the use of biological agents is considered quite safe. Three Trichoderma species viz. T. viride, T. harzionum and Trichoderma sp. (Local) were evaluated against Aspergillus niger, A. flavus, Alternaria tenuis, Fusarium oxysporium, Penicillium citrinum, Drechslera longirostrata and Fusarium solani. All the Trichoderma species were effective against above pathogens but Trichoderma (Local) proved to be superior for inhibition of the above pathogen as compared to other Trichoderma species.